Odpowiedzi

2009-11-29T14:44:50+01:00
(x-5)do kwadr. - (x+2) do kwadr.=7y
(y+4)do kwadr. - (y-2)(y+2)=8x

x do kwadr. + 10x + 25- x do kwadr. +4x +4=7y
y do kwadr. +8y +16-y do kwadr. - 4=8x

-6x+29=7y
8y+16-4=8x /:8

-6x+29=7y
y+1,5=x

-6(y +1,5)+29=7y
y+1,5=x

-6y-9+29=7y
y+1,5=x

-6y-7y=-20
y+1,5=x

-13y=-20 /:(-13)
y+1,5=x

y=1,54
1,54+1,5=x

y=1,54
x=3,04
2009-11-29T14:48:25+01:00
(x - 5)² - (x + 2)² = 7y
(y + 4)² - (y - 2)(y + 2) = 8x

x² - 10x + 25 - x² - 4x - 4 = 7y
y² + 8y + 16 - y² + 4 = 8x

-14x + 25 = 7y
8y + 20 = 8x / ÷ 8

-14x + 25 = 7y
y + 2,5 = x

-14 ( y + 2,5 ) + 25 = 7y
y + 2,5 = x

y + 2,5 = x
-14y - 35 + 25 = 7y

y + 2,5 = x
-14y - 7y = 10

y + 2,5 = x
-21y = 10 / ÷ -21

y = - 10/21 ≈ -0,5
-0,5 +2,5 = x

y= -0,5
x= 2